"By and for local people": assessing the connection between local energy plans and community energy. Issue 9 (2nd September 2019) - Wyse, Susan Morrissey; Hoicka, Christina E.
ABSTRACT: "Community energy" (CE) is argued to be an opportunity to transition to low-carbon energy systems while creating additional benefits for local communities. CE is defined as energy initiatives that place a high degree of emphasis on participation of local community members through ownership and control, where through doing so, benefits are created for the community. The trend has seen considerable growth in many countries over the last decade. Occurring simultaneously is a trend for local communities (e.g. municipalities) to create their own Local Energy Plans (LEPs) – a planning process that articulates energy-related actions (i.e. expected outcomes). While CE and LEPs both address energy activities in a local context, any further connection between these trends remains unclear. This research develops a framework, based on CE and LEP literature, to assess LEPs for their relevance to CE. The research analyses 77 LEPs from across Canada for the ways in which they address the three components that define CE: community participation, community ownership, and community capacity. The main findings are that LEPs have emerged as a process that is both relevant to CE and capable of strategically addressing its components. Despite this, LEPs do not appear to reveal a radically different approach to the "closed and institutional" models of traditional community involvement practices. The investigation suggests that for CE advocates, LEPs may be considered to be an important avenue to pursue CE ambitions. LEPs could increase their relevance to CE by improving the processes and actions related to all three CE components.